Silicon-tin-carbon composite material, preparation method thereof, pole piece and electrochemical device

By using cluster structure and graphene layer coating design in silicon-tin carbon composite materials, the problem of poor circulation performance of existing materials is solved, and higher electrochemical performance and better circulation stability are achieved. It is suitable for high-energy density lithium-ion batteries.

CN119695118APending Publication Date: 2025-03-25NINGBO SHANSHAN NEW MATERIAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411896690.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials have poor electrochemical performance, especially poor circulation performance, which is difficult to meet the needs of high energy density and fast charging of lithium-ion batteries.

Method used

A silicon-tin carbon composite material coated with a cluster structure and graphene layer is formed by a tin-based alloy frame, core-shell structure of silicon particles and the coating of carbon layer to form a multivariate three-dimensional structure, which improves the conductivity of the material and reduces the internal resistance of charge transfer.

Benefits of technology

It significantly improves the cyclic performance and electrochemical performance of silicon-tin-carbon composite materials, enhances the conductive and mechanical properties of the materials, and is suitable for high-energy-density lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a silicon-tin-carbon composite material, a preparation method thereof, a pole piece and an electrochemical device. The silicon-tin-carbon composite material comprises a cluster structure and a graphene layer coating the surface of the cluster structure, the cluster structure comprises a plurality of silicon-tin-carbon composite particles, and second gaps are distributed among the silicon-tin-carbon composite particles; each silicon-tin-carbon composite particle has a core-shell structure and comprises an inner core and a shell layer coating the inner core, and a first gap is distributed between the shell layer and the inner core; the inner core comprises a tin-based alloy frame and silicon particles, and the silicon particles are distributed in the tin-based alloy frame; the shell layer includes a carbon layer. The silicon-tin-carbon composite material disclosed by the invention has relatively good conductivity and relatively low charge transfer internal resistance. The battery assembled by the silicon-tin-carbon composite material has better electrochemical performance, and particularly has better cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-tin-carbon composite material and a preparation method thereof, a pole piece and an electrochemical device. Background Art

[0002] With the continuous development of lithium-ion battery technology, its specific capacity, energy density and cycle life stability have been greatly improved, promoting the development of hybrid and electric vehicle markets. However, the growing demand for high energy density and fast charging of lithium-ion batteries has posed new challenges to the development of negative electrode materials. Graphite is increasingly unable to meet the needs of the new era due to its inherent limitations of low theoretical capacity. At present, silicon is one of the most promising materials to replace graphite negative electrodes due to its theoretical capacity close to 4200mAh / g. However, the severe volume expansion of silicon during charging and discharging (>300%) leads to its poor cycle performance, affecting the development of silicon and its alloy materials and hindering its application in commercial batteries. So far, researchers have mainly focused on the design of advanced electrode structures, especially including the development of silicon nanoparticles and their encapsulation into carbon matrices. It has been proven that advanced structural design can suppress the volume expansion of silicon materials.

[0003] Chinese patent application CN 118373427A introduces a pre-magnesium silicon oxide negative electrode material, a preparation method thereof and a lithium ion battery; providing a magnesium-embedded silicon oxide material; crushing the magnesium-embedded silicon oxide material and heating it in vacuum, cooling it to obtain a magnesium-containing silicon oxide material; heating the magnesium-containing silicon oxide material under the protection of an inert atmosphere, and coating the surface of the magnesium-containing silicon oxide material with a carbon source gas to form a coating layer, thereby obtaining a pre-magnesium silicon oxide negative electrode material. However, the cycle performance of the negative electrode material still needs to be further improved.

[0004] Therefore, it is urgent to propose a scalable preparation method to construct a multi-dimensional three-dimensional structure, comprehensively improve the performance of silicon materials, and show excellent performance in cycle performance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defects of poor electrochemical performance, especially poor cycle performance, of silicon-carbon composite materials in the prior art, and provide a silicon-tin-carbon composite material and its preparation method, pole piece and electrochemical device. The silicon-tin-carbon composite material of the present invention has better electrical conductivity and lower charge transfer internal resistance. The battery assembled from the silicon-tin-carbon composite material has better electrochemical performance, especially better cycle performance. The preparation method of the tin-carbon composite material of the present invention is simple, highly practical, does not involve a large amount of chemical reagents, and can be operated on a large scale.

[0006] The present invention solves the above technical problems through the following solutions.

[0007] The present invention provides a silicon-tin-carbon composite material, which comprises a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure comprises a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0008] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core, and a first gap is distributed between the shell layer and the core; wherein the core includes a tin-based alloy frame and silicon particles, and the silicon particles are distributed in the tin-based alloy frame; the shell layer includes a carbon layer.

[0009] In the present invention, the "several" means at least 2.

[0010] In the present invention, the D50 of the silicon-tin-carbon composite material may be 400-550 nm, preferably 430-520 nm, for example 485, 481, 480, 475, 474, 470 or 465 nm.

[0011] In the present invention, the average pore size of the silicon-tin-carbon composite material may be 14-30 nm, preferably 17-27 nm, for example, 23.7, 23.4, 22.7, 22.4, 22.1, 21.7, 21.6, 21.2, 20.7, 20.6, 20.4, 20.3 or 19.2 nm.

[0012] In the present invention, the silicon content of the silicon-tin-carbon composite material may be 45%-50%, preferably 46%-49%, for example 33.1%, 33.0%, 32.8%, 32.7%, 32.6%, 32.5%, 32.3%, 32.2%, 32.1%, 31.9%, 31.7%, 31.3% or 31.2%.

[0013] In the present invention, the tin content of the silicon-tin-carbon composite material may be 12%-24%, preferably 15%-21%, for example 19.1%, 18.7%, 18.6%, 18.5%, 18.4%, 18.3%, 18.2%, 17.9%, 17.8%, 17.6%, 17.5%, 17.4% or 17.3%.

[0014] In the present invention, the carbon content of the silicon-tin-carbon composite material may be 18%-30%, preferably 20%-28%, for example 25.1%, 24.8%, 24.6%, 24.3%, 24.2%, 24.1%, 23.9%, 23.8%, 23.7%, 23.6% or 23.2%.

[0015] In the present invention, the oxygen content of the silicon-tin-carbon composite material may be 4%-10%, preferably 6%-8%, for example 7.86%, 7.69%, 7.56%, 7.55%, 7.42%, 7.30%, 7.06%, 7.02%, 6.99%, 6.82%, 6.75%, 6.68%, 6.57%, 6.54%, 6.43%, 6.35% or 6.30%.

[0016] The content of each element mentioned above represents the percentage of the mass of each element to the mass of the silicon-tin-carbon composite material.

[0017] In the present invention, in a single silicon-tin-carbon composite particle, the tin-based alloy framework preferably further includes a second metal. The type of the second metal can be one or more of indium, platinum, iron, cobalt, germanium, antimony, palladium, nickel, cobalt and copper, such as indium and nickel.

[0018] Among them, when the second metal is indium and nickel, the indium content may be 3%-15%, preferably 6%-12%, for example, 9.5%, 9.4%, 9.3%, 9.2%, 9.1%, 8.9% or 8.8%; the nickel content may be 20.4%-44.4%, preferably 25%-28%, for example, 9.5%, 9.4%, 9.3%, 9.2%, 9.1%, 8.7% or 8.6%; the indium or nickel content is the percentage of the mass of indium or nickel to the mass of the silicon-tin-carbon composite material.

[0019] In the present invention, in the single silicon-tin-carbon composite particle, the shell layer preferably further includes a silicon-containing layer, the silicon-containing layer covers the core, the carbon layer covers the silicon-containing layer, and a first gap is distributed between the silicon-containing layer and the carbon layer.

[0020] In the present invention, in the single silicon-tin-carbon composite particle, the carbon layer preferably further includes heteroatoms.

[0021] The heteroatom may be one or more of nitrogen, phosphorus, sulfur and boron, such as nitrogen.

[0022] The heteroatom content may be 0.1-0.65%, preferably 0.2%-0.55%, such as 0.34%, 0.32%, 0.31%, 0.30%, 0.28%, 0.27%, 0.26%, 0.25%, 0.24%, 0.23% or 0.21%. The heteroatom content represents the percentage of the mass of the heteroatom to the mass of the silicon-tin-carbon composite material.

[0023] The present invention also provides a method for preparing a silicon-tin-carbon composite material, which comprises the following steps:

[0024] S1, subjecting a mixed solution including tin chloride, transition metal cyanide and silicon source to reduction reaction, drying and annealing to obtain a first precursor;

[0025] S2, coating the first precursor with silicon dioxide to form a silicon dioxide layer to obtain a second precursor; mixing the aqueous dispersion of the second precursor with an oil phase solution containing an emulsifier, removing the solvent and performing heat treatment to obtain a third precursor;

[0026] S3, carbon-coating the third precursor, removing the silicon dioxide layer, and obtaining a fourth precursor;

[0027] S4, coating the fourth precursor with graphene to obtain a silicon-tin-carbon composite material.

[0028] In S1 of the present invention, the transition metal cyanide refers to a transition metal element and a cyanide ion (CN - ) form a compound with a molecular formula of A y M k (CN) z , A represents alkali metal ion, M represents central metal ion, and CN represents cyanide ion.

[0029] The alkali metal ion A may be sodium, potassium or lithium.

[0030] Here, y may be a natural number satisfying 0<y<3, such as 2.

[0031] The type of the central metal ion M may be one or more of iron, cobalt, copper, nickel and platinum, such as nickel, copper or platinum.

[0032] Herein, k may be a natural number satisfying 0<y<2, such as 1.

[0033] Herein, z may be a natural number satisfying 2<z<9, such as 3 or 4.

[0034] In S1 of the present invention, the transition metal cyanide is preferably one or more of potassium ferrocyanide, potassium ferrocyanide, potassium cobalt cyanide, potassium nickel cyanide, trisodium cuprous cyanide and dilithium platinum (IV) cyanide, such as potassium nickel cyanide (K2Ni(CN)4), trisodium cuprous cyanide (Na2[Cu(CN)3]) or dilithium platinum (IV) cyanide (Li2Pt(CN)4).

[0035] In S1 of the present invention, the silicon source may be a conventional silicon-containing substance in the art, preferably one or more of silicon powder, silicon oxide and silicon monoxide, such as silicon powder.

[0036] In S1 of the present invention, the D50 of the silicon source may be 50-100 nm, for example 75 nm.

[0037] In S1 of the present invention, the molar ratio of tin in the tin chloride to the transition metal in the transition metal cyanide may be (1-2):(0.5-1), preferably (1.5-2):(0.8-1), for example 2:1.

[0038] In S1 of the present invention, the molar mass ratio of tin in the tin chloride to the silicon source may be (0.1-0.5) mol:240 g, for example, 0.36 mol:240 g.

[0039] In S1 of the present invention, the solvent in the mixed solution of tin chloride, transition metal cyanide and silicon source can be a conventional solvent in the art that can dissolve tin chloride, transition metal cyanide and silicon source, such as ethanol.

[0040] In S1 of the present invention, the mixed solution of tin chloride, transition metal cyanide and silicon source is preferably obtained by the following steps: dispersing the silicon source in a transition metal cyanide solution to obtain a first solution, and then mixing it with the tin chloride solution.

[0041] In the transition metal cyanide solution, the molar concentration of the transition metal cyanide may be 0.5-0.7 mol / L, for example 0.6 mol / L. In the first solution, the mass concentration of the silicon source may be 80-100 mg / mL, for example 80 mg / mL. The molar concentration of the tin chloride solution may be 0.5-0.7 mol / L, for example 0.6 mol / L.

[0042] In S1 of the present invention, a reducing agent is generally added in the reduction reaction. The reducing agent used in the reduction reaction may be one or more of sodium borohydride, lithium borohydride, lithium aluminum hydride and nickel borohydride, such as sodium borohydride.

[0043] In S1 of the present invention, the reducing agent used in the reduction reaction is preferably added in the form of a reducing agent solvent. The molar concentration of the reducing agent solution may be 1-5M, for example 2M.

[0044] In S1 of the present invention, the reduction reaction time may be 1-1.5 h, for example 1 h.

[0045] In S1 of the present invention, the drying operation may be conventional in the art, such as freeze drying, supercritical drying or vacuum drying. The freeze drying temperature may be -30 to -80°C, for example -60°C. The freeze drying time may be 3-7h, for example 4h. The supercritical drying temperature may be 10-40°C, for example 20 or 30°C. The supercritical drying time may be 1-3h, for example 1.5 or 2h. During the supercritical drying, the pressure of the system may be 10-15kPa, for example 10kPa. The vacuum drying temperature may be 80-100°C, for example 90°C. The vacuum drying time may be 18-24h, for example 20h.

[0046] In S1 of the present invention, the temperature of the annealing treatment may be 650-900° C., such as 700, 750, 800 or 850° C. The rate of heating from room temperature to the temperature of the annealing treatment may be 1-10° C. / min, such as 3° C. / min. The time of the annealing treatment may be 5-8 h, such as 6 h.

[0047] In S1 of the present invention, the annealing treatment generally further includes washing and drying steps in sequence.

[0048] The washing operation may be conventional in the art, such as washing with distilled water and ethanol.

[0049] The drying operation may be conventional in the art, such as vacuum drying. The drying temperature may be 70-90° C., such as 80° C. The drying time may be 1-3 h, such as 1 h.

[0050] In S1 of the present invention, the mixed solution including tin chloride, transition metal cyanide and silicon source preferably also includes a second metal chloride. The second metal chloride can be a conventional metal chloride in the art except tin chloride, preferably one or more of indium chloride, platinum chloride, ferric chloride, cobalt chloride, germanium chloride, antimony chloride and palladium chloride, such as indium chloride.

[0051] The molar ratio of tin in the tin chloride to the second metal in the second metal chloride is preferably (1-2):(0.5-1), more preferably (1.5-2):(0.6-1.2), for example 2:1 or 2:0.8.

[0052] In S1 of the present invention, after the annealing treatment, it is preferred to further include coating with a silicon-containing layer. The coating with the silicon-containing layer can be performed by subjecting silicon source gas to chemical vapor deposition or atomic layer deposition.

[0053] Wherein, when the silicon-containing layer is coated, the type of silicon source gas may be one or more of tetraethoxysilane, methylsilane and ethylsilane, such as methylsilane. When the silicon-containing layer is coated, the working temperature may be 150-350°C, such as 250 or 300°C. When the silicon-containing layer is coated, the coating time may be 24-48h, such as 30h. When the silicon-containing layer is coated, the flow rate of the silicon source gas may be 50-100mL / min, such as 80mL / min. The mass volume ratio of the product obtained after the annealing treatment and the silicon source gas may be 5g: (7200-28800)mL, such as 5g: 14400mL. When the silicon-containing layer is coated, the number of cycles may be 180-300 times, such as 220 or 240 times.

[0054] In S1 of the present invention, the structure of the first precursor may include a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework.

[0055] In S1 of the present invention, preferably, the structure of the first precursor includes a tin-based alloy framework, silicon particles, and a silicon-containing layer, the silicon particles are distributed in the tin-based alloy framework, and the silicon-containing layer covers the tin-based alloy framework and the silicon particles.

[0056] In S2 of the present invention, the method for preparing the first precursor by coating it with silicon dioxide preferably comprises the following steps: mixing the first precursor, a silicon source and an ammonia solution, acid washing, and heat treatment.

[0057] The type of silicon source can be conventional in the art, preferably silicate or silicate. The silicate is preferably ethyl orthosilicate and / or methyl orthosilicate. The silicate is preferably one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate.

[0058] The mass percentage of ammonia in the ammonia solution is preferably 25%-30%, for example 28%.

[0059] The mass volume ratio of the first precursor, the silicon source and the aqueous ammonia solution is preferably (2-5) g: (3-10) mL: (240-260) mL, for example 3 g: 8 mL: 250 mL.

[0060] The mixing time is preferably 40-60 min, such as 55 min.

[0061] The acid used for pickling can be a conventional inorganic acid in the art, such as hydrochloric acid. The pickling generally uses an aqueous solution of an acid, such as an aqueous solution of an acid with a molar concentration of 2M.

[0062] After the acid washing and before the heat treatment, it is preferred to further include conventional steps of filtration, washing and drying in the art.

[0063] The temperature of the heat treatment is preferably 500-750° C., such as 600, 650 or 700° C. The time of the heat treatment is preferably 8-24 hours, such as 15 hours. The rate of heating from room temperature to the temperature of the second heat treatment is preferably 1-10° C. / min, such as 3° C. / min.

[0064] In S2 of the present invention, the structure of the second precursor may include a first precursor and a silicon dioxide layer covering the first precursor; the first precursor includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework.

[0065] In S2 of the present invention, preferably, the structure of the second precursor includes a first precursor and a silicon dioxide layer coating the first precursor; the first precursor includes a tin-based alloy frame, silicon particles, and a silicon-containing layer, the silicon particles are distributed in the tin-based alloy frame, and the silicon-containing layer coats the tin-based alloy frame and the silicon particles.

[0066] In the present invention S2, the aqueous dispersion of the second precursor preferably comprises the second precursor, a surfactant and water.

[0067] Among them, the type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide.

[0068] The ratio of the second precursor, the surfactant and the water is preferably (8-12) g: (0.3-0.8) mol: 300 mL, for example 10 g: 0.55 mol: 300 mL.

[0069] In S2 of the present invention, the type of the emulsifier may be an emulsifier having a hydrophile-lipophile balance (HLB) of 3-8, preferably an emulsifier having a hydrophile-lipophile balance (HLB) of 4-7, and more preferably one or more of propylene glycol fatty acid ester, diethylene glycol monooleate, glyceryl monostearate and diethylene glycol monolaurate, such as diethylene glycol monooleate or propylene glycol fatty acid ester.

[0070] In S2 of the present invention, the type of the oil phase solvent in the oil phase solution containing the emulsifier can be conventional in the art, and is preferably an olefin having 12 to 28 carbon atoms, such as 1-octadecene.

[0071] In S2 of the present invention, the mass percentage of the emulsifier in the oil phase solution containing the emulsifier may be 0.5-1.0wt%, preferably 0.6-0.9wt%, for example 0.8wt%.

[0072] In S2 of the present invention, the mass ratio of the second precursor to the emulsifier may be 10:(0.15-0.30), for example, 10:0.18 or 10:0.24.

[0073] In S2 of the present invention, the method for removing the solvent may be conventional in the art, such as evaporation. The temperature during the evaporation may be 95-98°C.

[0074] In S2 of the present invention, the temperature of the heat treatment is preferably 450-600° C., such as 550° C. The time of the heat treatment is preferably 0.5-1.5 h, such as 1 h. The heat treatment is preferably performed in an air atmosphere.

[0075] In S2 of the present invention, the heat treatment preferably further includes a condensation step.

[0076] In S2 of the present invention, the structure of the third precursor may include a second precursor distributed in a cluster structure, and the structure of the second precursor includes a first precursor and a silicon dioxide layer covering the first precursor; the first precursor includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework.

[0077] In S2 of the present invention, preferably, the structure of the third precursor includes a second precursor distributed in a cluster structure, and the structure of the second precursor includes a first precursor and a silicon dioxide layer coating the first precursor; the first precursor includes a tin-based alloy framework, silicon particles, and a silicon-containing layer, the silicon particles are distributed in the tin-based alloy framework, and the silicon-containing layer coats the tin-based alloy framework and the silicon particles.

[0078] In S3 of the present invention, the carbon coating temperature may be 500-900° C., such as 650 or 700° C. The carbon coating time may be 8-24 hours, such as 15 hours.

[0079] In S3 of the present invention, the type of carbon source for carbon coating can be conventional in the art, preferably phenolic resin and / or asphalt, such as phenolic resin fixed by surfactant.

[0080] Wherein, when the type of the carbon source is phenolic resin, the preparation method of carbon-coating the third precursor preferably comprises the following steps: mixing resorcinol, formaldehyde, a catalyst and the third precursor, polymerization reaction and carbon coating.

[0081] The molar ratio of the formaldehyde to the resorcinol may be (500-1500): (0.5-1.5), for example, 1000: 1 or 625: 1. The catalyst may be a base, preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium carbonate. The molar ratio of the resorcinol to the catalyst may be (0.5-1.5): (0.007-0.03), for example, 0.5: 0.009 or 0.8: 0.009. The molar mass ratio of the resorcinol to the third precursor is preferably (0.5-1.5) mmol: (3-4.5) g, for example, 0.5 mmol: 4.0 g, 0.8 mmol: 4.0 g or 0.5 mmol: 3.5 g. The temperature of the polymerization reaction may be 80-100° C., for example, 85 or 90° C. The time of the polymerization reaction may be 8-24 h, for example, 15 h. After the polymerization reaction and before the carbon coating, a drying step is preferably further included. Wherein, the drying operation may be conventional in the art, such as freeze drying, supercritical drying or vacuum drying. The freeze drying temperature may be -30 to -80°C, for example -60°C. The freeze drying time may be 3-7h, for example 4h. The supercritical drying temperature may be 10-40°C, for example 20 or 30°C. The supercritical drying time may be 1-3h, for example 1.5 or 2h. During the supercritical drying, the pressure of the system may be 10-15kPa, for example 10kPa. The vacuum drying temperature may be 80-100°C, for example 90°C. The vacuum drying time may be 10-20h, for example 18h.

[0082] Among them, when the type of the carbon source is a phenolic resin fixed with a surfactant, the preparation method of carbon-coating the third precursor preferably includes the following steps: mixing an aqueous solution of a surfactant, resorcinol, formaldehyde, a catalyst and a third precursor, polymerization reaction and carbon coating.

[0083] The type of the surfactant is preferably one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, cetyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, for example cetyltrimethylammonium bromide.

[0084] In the aqueous solution of the surfactant, the molar ratio of the surfactant to the water is preferably (0.3-0.65):(6000-12000), for example 0.45:8000 or 0.55:8000.

[0085] The molar ratio of the surfactant to the resorcinol is preferably (0.3-0.65):(0.5-1.5), such as 0.45:0.5, 0.55:0.5 or 0.45:0.8.

[0086] In S3 of the present invention, the carbon source is preferably further added with heteroatoms during the carbon coating.

[0087] Among them, when heteroatoms are added to the carbon source during the carbon coating, the preparation method of carbon coating the third precursor preferably includes the following steps: mixing the heteroatom source, resorcinol, formaldehyde, a catalyst and the third precursor, polymerization reaction and carbon coating.

[0088] The type of the heteroatom may be one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen. When the type of the heteroatom is nitrogen, the type of the nitrogen source may be a nitrogen-containing substance, preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as melamine.

[0089] The molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-1.5), for example 0.03:0.8 or 0.03:0.5.

[0090] In S3 of the present invention, the method for removing the silicon dioxide layer may be etching. The etching solution used for the etching is preferably a hydrofluoric acid solution. The mass percentage of hydrofluoric acid in the hydrofluoric acid solution is preferably 4-6wt%, such as 5wt%.

[0091] In S3 of the present invention, the structure of the fourth precursor may include a cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0092] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core, and a first gap is distributed between the shell layer and the core; wherein the core includes a tin-based alloy frame and silicon particles, and the silicon particles are distributed in the tin-based alloy frame; the shell layer includes a carbon layer.

[0093] In S3 of the present invention, preferably, the structure of the fourth precursor may include a cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0094] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core, and a first gap is distributed between the shell layer and the core; wherein the core includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework; the shell layer includes a carbon layer, and the carbon layer also includes heteroatoms.

[0095] In S3 of the present invention, preferably, the structure of the fourth precursor includes a cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0096] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core; the core includes a tin-based alloy frame and silicon particles, the silicon particles are distributed in the tin-based alloy frame, and the shell layer includes a silicon-containing layer and a carbon layer in sequence along the direction away from the core; a first gap is distributed between the silicon-containing layer and the carbon layer.

[0097] In S3 of the present invention, preferably, the structure of the fourth precursor includes a cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0098] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core; the core includes a tin-based alloy framework and silicon particles, the silicon particles are distributed in the tin-based alloy framework, and the shell layer includes a silicon-containing layer and a carbon layer in sequence along the direction away from the core; a first gap is distributed between the silicon-containing layer and the carbon layer; the carbon layer also includes heteroatoms.

[0099] In S4 of the present invention, the carbon source used for the graphene carbon coating may be a conventional carbon source capable of forming graphene in the art, preferably humic acid.

[0100] Among them, when the carbon source is humic acid, the graphene carbon coating is preferably performed by first mixing the fourth precursor, humic acid and water, and then dropping an ammonia solution under stirring conditions to remove the solvent.

[0101] The amount of water used is not limited, so that the solid-liquid ratio in the mixed solution of the fourth precursor, humic acid and water is preferably 1:(10-15), for example 1:12.

[0102] The ammonia content in the aqueous ammonia solution is preferably 25%-30%, for example 28%. The amount of the aqueous ammonia solution used is not limited, as long as the humic acid powder is completely dissolved.

[0103] The method for removing the solvent may be conventional in the art, such as evaporation. The temperature during the evaporation may be 80-100°C, such as 90°C.

[0104] In S4 of the present invention, the mass ratio of the fourth precursor to the carbon source during the graphene carbon coating may be 100:(10-18), preferably 100:(11-18), for example 100:15 or 100:12.

[0105] In S4 of the present invention, the graphene carbon coating is preferably subjected to a first-stage sintering, cooling and a second-stage sintering, and the temperature of the second-stage sintering is higher than the temperature of the first-stage sintering.

[0106] The temperature of the first sintering step is preferably 200-350°C, such as 260 or 280°C. The time of the first sintering step is preferably 6-12h, such as 8h. The first sintering step is preferably performed in a microwave oven. The power of the microwave oven can be 800-1100W, such as 1000W.

[0107] The end point of the cooling may be room temperature, generally 20-30°C.

[0108] Wherein, the temperature of the second stage sintering is preferably 600-900°C, such as 700 or 750°C. The time of the second stage sintering is preferably 8-24h, such as 15h. The rate of heating from room temperature to the temperature of the second stage sintering can be 1-10°C / min, such as 3°C / min. The second stage sintering is preferably carried out in a tubular furnace. The second stage sintering is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen.

[0109] In S4 of the present invention, the silicon-tin-carbon composite material may include a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0110] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core, and a first gap is distributed between the shell layer and the core; wherein the core includes a tin-based alloy frame and silicon particles, and the silicon particles are distributed in the tin-based alloy frame; the shell layer includes a carbon layer.

[0111] In S4 of the present invention, preferably, the silicon-tin-carbon composite material comprises a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure comprises a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0112] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core, and a first gap is distributed between the shell layer and the core; wherein the core includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework; the shell layer includes a carbon layer, and the carbon layer also includes heteroatoms.

[0113] In S4 of the present invention, preferably, the silicon-tin-carbon composite material comprises a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure comprises a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0114] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core; the core includes a tin-based alloy frame and silicon particles, the silicon particles are distributed in the tin-based alloy frame, and the shell layer includes a silicon-containing layer and a carbon layer in sequence along the direction away from the core; a first gap is distributed between the silicon-containing layer and the carbon layer.

[0115] In S4 of the present invention, preferably, the silicon-tin-carbon composite material comprises a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure comprises a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0116] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core; the core includes a tin-based alloy framework and silicon particles, the silicon particles are distributed in the tin-based alloy framework, and the shell layer includes a silicon-containing layer and a carbon layer in sequence along the direction away from the core; a first gap is distributed between the silicon-containing layer and the carbon layer, and the carbon layer also includes heteroatoms.

[0117] The present invention provides a silicon-tin-carbon composite material, which is prepared by the preparation method of the silicon-tin composite material as mentioned above.

[0118] The present invention also provides a pole piece, which comprises the silicon-tin-carbon composite material as described above.

[0119] The present invention also provides an electrochemical device, which comprises the pole piece as described above.

[0120] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0121] The reagents and raw materials used in the present invention are commercially available.

[0122] The positive and progressive effects of the present invention are:

[0123] (1) The silicon-tin-carbon composite material of the present invention includes a cluster structure and a graphene layer, wherein the cluster structure includes a plurality of silicon-tin-carbon composite particles; the core of a single silicon-tin-carbon composite particle includes a tin-based alloy framework and silicon particles, and the shell layer includes a carbon layer, and there is a gap between the core and the shell layer; first, the tin-based alloy framework has a unique three-dimensional structure, which can greatly improve the volume expansion of silicon particles; in addition, the metal elements in the tin-based alloy framework can improve the electrical conductivity of the material; secondly, the gap between the core and the shell layer provides another guarantee for the expansion of silicon particles; furthermore, gaps are distributed between a plurality of silicon-tin-carbon composite particles, which further effectively alleviates the volume expansion of silicon particles; finally, the good mechanical properties and conductive properties of the graphene layer can further guarantee the volume expansion of silicon particles, while effectively improving the electrochemical properties of the material.

[0124] (2) The battery assembled from the silicon-tin-carbon composite material has better electrochemical performance, especially better cycle performance.

[0125] (3) The preparation method of the silicon-tin-carbon composite material of the present invention is simple, does not require the involvement of a large amount of chemical reagents, is highly practical, can be operated on a large scale, and is easy to industrialize. DETAILED DESCRIPTION

[0126] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0127] Example 1

[0128] S1. Preparation of the first precursor:

[0129] (1) First, a 0.6 mol / L SnCl4 ethanol solution (Solution A) and a 0.6 mol / L InCl3 ethanol solution (Solution B) were obtained by conventional methods. Then, 240 g of silicon powder (D50: 75 nm) was ultrasonically dispersed in a 0.6 mol / L K2Ni(CN)4 ethanol solution (Solution C) to obtain Solution D. The mass concentration of silicon powder in Solution D was 80 mg / mL.

[0130] (2) Solution A, Solution B and Solution D were mixed at 20°C in a molar ratio of Sn, In and Ni of 2:1:1 (the molar mass ratio of tin to silicon powder was 0.36 mol:240 g), and a 2 mol / L sodium borohydride solution was added for reduction reaction for 1 h. The obtained product was vacuum dried at 90°C for 20 h, and heated to 700°C at a rate of 3°C / min, and annealed for 6 h. The annealed product was then repeatedly washed with distilled water and ethanol, and then dried (vacuum dried at 80°C for 1 h).

[0131] (3) Using 50 g of the material obtained in step S1 (2) as a base template, methylsilane with a flow rate of 80 mL / min and silicon source gas were introduced into a Beneq TFS 200 atomic layer deposition (ALD) device at a working temperature of 250°C for 30 hours and 240 cycles. After stopping the cycle, an inert gas was used to purge the residual impurity gas and the temperature was quickly cooled to room temperature to obtain a first precursor. The structure of the first precursor includes a tin-based alloy frame, silicon particles, and a silicon-containing layer. The silicon particles are distributed in the tin-based alloy frame, and the silicon-containing layer covers the tin-based alloy frame and the silicon particles.

[0132] S2, preparation of the second precursor: (1) 8 mL of silicon source (ethyl orthosilicate) and 3 g of the first precursor obtained in step S1 were added with 250 mL of 28 wt% ammonia solution, mixed and stirred for 55 min, filtered and cleaned, and pickled with 2 mol / L hydrochloric acid, filtered and cleaned again, and dried; then, at 600 ° C, the heating rate was 3 ° C / min, and the silicon dioxide layer was fixed by heat treatment for 15 h to obtain the second precursor. The structure of the second precursor includes the first precursor and the silicon dioxide layer covering the first precursor; the first precursor includes a tin-based alloy frame and silicon particles, and a silicon-containing layer, the silicon particles are distributed in the tin-based alloy frame, and the silicon-containing layer covers the tin-based alloy frame and the silicon particles.

[0133] Preparation of the third precursor: (2) 10 g of the second precursor is uniformly dispersed in 300 mL of deionized water containing 0.55 mol of a surfactant (hexadecyltrimethylammonium bromide) to form an aqueous dispersion, and mixed with 300 mL of a 1-octadecene solution of 0.8 wt% diethylene glycol monooleate to form an oil-in-water emulsion. After evaporating the solvent at 95-98 ° C, the mixture is collected by centrifugation, and then heat-treated at 550 ° C for 1 h in an air atmosphere to remove organic matter, and then condensed to form a third precursor. The structure of the third precursor includes the second precursor distributed in a clustered structure, the structure of the second precursor includes the first precursor and a silicon dioxide layer covering the first precursor; the first precursor includes a tin-based alloy framework and silicon particles, and a silicon-containing layer, the silicon particles are distributed in the tin-based alloy framework, and the silicon-containing layer covers the tin-based alloy framework and the silicon particles.

[0134] S3, preparation of the fourth precursor: 0.45mmol surfactant (hexadecyltrimethylammonium bromide) and 8mol deionized water were mixed and ultrasonically dispersed for 55min to form spherical micelles. Then, a mixture of melamine (0.03mmol), resorcinol (0.5mmol), formaldehyde (0.5mol) and sodium carbonate (0.009mmol) was added and stirred continuously. Subsequently, 4g of the third precursor obtained in step S2 (2) was added, and then polymerized at 90℃ for 15h, and then vacuum dried at 90℃ for 18h, and then carbon coated at 650℃ for 15h under nitrogen atmosphere. Finally, the silicon dioxide layer was removed with 5wt% HF solution to obtain the fourth precursor. The structure of the fourth precursor includes a cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles;

[0135] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core; the inner core includes a tin-based alloy frame and silicon particles, the silicon particles are distributed in the tin-based alloy frame, and the shell layer includes a silicon-containing layer and a carbon layer in sequence along the direction away from the inner core; a first gap is distributed between the silicon-containing layer and the carbon layer; the carbon layer also includes nitrogen doping.

[0136] S4, adding the fourth precursor prepared in step S3 and humic acid (model 53680-10G, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) into deionized water at a mass ratio of 100:15 and mixing evenly, controlling the solid-liquid ratio at 1:12, then dripping a 28wt% ammonia solution under stirring until the humic acid powder is completely dissolved, heating to 90°C and evaporating the solvent to make the humic acid evenly coat the fourth precursor; and sintering at 260°C in a microwave oven (microwave power of 1000W) for 8h, cooling to room temperature, taking out, and then placing in a tubular furnace under a nitrogen atmosphere and heating from room temperature to 700°C at a rate of 3°C / min for 15h, so that the humic acid is thermally decomposed to synthesize graphene in situ, and obtain a silicon-tin-carbon composite material. The silicon-tin-carbon composite material includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles; wherein a single silicon-tin-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer coating the inner core, the inner core includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework; the shell layer includes a silicon-containing layer and a carbon layer in sequence along a direction away from the inner core; a first gap is distributed between the silicon-containing layer and the carbon layer, and the carbon layer also includes nitrogen doping.

[0137] Example 2

[0138] The difference from Example 1 is that the molar ratio of Sn, In and Ni in step S1 (2) is 2:0.8:1.

[0139] Example 3

[0140] The difference from Example 1 is that the annealing temperature in step S1 (2) is 750°C.

[0141] Example 4

[0142] The difference from Example 1 is that the atomic layer deposition operating temperature in step S1 (3) is 300°C.

[0143] Example 5

[0144] The difference from Example 1 is that the number of atomic layer deposition cycles in step S1 (3) is 220 times.

[0145] Example 6

[0146] The difference from Example 1 is that the heat treatment temperature in step S2 (1) is 650°C.

[0147] Example 7

[0148] The difference from Example 1 is that in step S2 (2), a 0.6 wt % diethylene glycol monooleate 1-octadecene solution is used.

[0149] Example 8

[0150] The difference from Example 1 is that the emulsifier in step S2 (2) is propylene glycol fatty acid ester.

[0151] Example 9

[0152] The difference from Example 1 is that the surfactant in step S3 is 0.55 mmol.

[0153] Example 10

[0154] The difference from Example 1 is that 0.8 mmol of resorcinol is added in step S3.

[0155] Embodiment 11

[0156] The difference from Example 1 is that 3.5 g of the third precursor is added in step S3.

[0157] Example 12

[0158] The difference from Example 1 is that the polymerization temperature in step S3 is 85°C.

[0159] Embodiment 13

[0160] The difference from Example 1 is that the temperature of carbon coating in step S3 is 700°C.

[0161] Embodiment 14

[0162] The difference from Example 1 is that in step S4, the mass ratio of the fourth precursor to humic acid is 100:12.

[0163] Embodiment 15

[0164] The difference from Example 1 is that the temperature of the first sintering in step S4 is 280°C.

[0165] Example 16

[0166] The difference from Example 1 is that the temperature of the secondary sintering in step S4 is 750°C.

[0167] Embodiment 17

[0168] S1. Preparation of the first precursor:

[0169] (1) First, a 0.6 mol / L SnCl4 ethanol solution (solution A) and a 0.6 mol / L InCl3 ethanol solution (solution B) were obtained by conventional methods. Then, silicon powder was ultrasonically dispersed in a 0.6 mol / L K2Ni(CN)4 ethanol solution (solution C) to obtain solution D. The mass concentration of silicon powder in solution D was 80 mg / mL.

[0170] (2) Solution A, solution B and solution D were mixed at 20°C in a molar ratio of Sn, In and Ni of 2:1:1, and a 2 mol / L sodium borohydride solution was added for a reduction reaction for 1 hour. The obtained product was vacuum dried at 90°C for 20 hours, and the temperature was raised to 700°C at a rate of 3°C / min, and annealed for 6 hours. The annealed product was then repeatedly washed with distilled water and ethanol, and then dried to obtain a first precursor. The structure of the first precursor includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework.

[0171] S2, preparation of the second precursor: (1) 8 mL of silicon source and 3 g of the first precursor obtained in step S1 were added with 250 mL of 28 wt% ammonia solution, mixed and stirred for 55 min, filtered and cleaned, and pickled with 2 mol / L hydrochloric acid, filtered and cleaned again, and dried; then, at 600 ° C, the heating rate was 3 ° C / min, and the silicon dioxide layer was fixed by heat treatment for 15 h to obtain the second precursor. The structure of the second precursor includes a first precursor and a silicon dioxide layer covering the first precursor; the first precursor includes a tin-based alloy frame and silicon particles, and the silicon particles are distributed in the tin-based alloy frame.

[0172] Preparation of the third precursor: (2) 10 g of the second precursor is uniformly dispersed in 300 mL of deionized water containing 0.55 mol of a surfactant (hexadecyltrimethylammonium bromide) to form an aqueous dispersion, and mixed with 300 mL of a 1-octadecene solution of 0.8 wt% diethylene glycol monooleate to form an oil-in-water emulsion. After evaporating the solvent at 95-98 ° C, the mixture is collected by centrifugation, and then heat-treated at 550 ° C for 1 h in an air atmosphere to remove organic matter, and then condensed to form a third precursor. The structure of the third precursor includes the second precursor distributed in a clustered structure, and the structure of the second precursor includes the first precursor and a silicon dioxide layer covering the first precursor; the first precursor includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework.

[0173] S3, preparation of the fourth precursor: 0.45mmol surfactant (hexadecyltrimethylammonium bromide) and 8mol deionized water were mixed and ultrasonically dispersed for 55min to form spherical micelles. Then, a mixture of resorcinol (0.5mmol), formaldehyde (0.5mol) and sodium carbonate (0.009mmol) was added and stirred continuously. Subsequently, 4g of the third precursor obtained in step S2 (2) was added, and then polymerized at 90℃ for 15h, and then vacuum dried at 90℃ for 18h, and then carbon coated at 650℃ for 15h under nitrogen atmosphere. Finally, the silicon dioxide layer was removed with 5wt% HF solution to obtain the fourth precursor. The structure of the fourth precursor includes a cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles; wherein a single silicon-tin-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core; the inner core includes a tin-based alloy framework and silicon particles, the silicon particles are distributed in the tin-based alloy framework, and the shell layer includes a carbon layer; first gaps are distributed between the inner core and the carbon layer.

[0174] S4. The fourth precursor prepared in step S3 and humic acid are added to deionized water at a mass ratio of 100:15, and the mixture is evenly mixed. The solid-liquid ratio is controlled at 1:12. Then, a 28wt% ammonia solution is added dropwise under stirring until the humic acid powder is completely dissolved. The mixture is heated to 90°C and the solvent is evaporated to dryness, so that the humic acid is evenly coated on the surface of the fourth precursor. The mixture is sintered at 260°C for 8h in a microwave oven (microwave power is 1000W), cooled to room temperature, taken out, and then placed in a tubular furnace under an inert atmosphere and heated from room temperature to 700°C at a rate of 3°C / min, and sintered for 15h in a second stage, so that the humic acid is thermally decomposed to synthesize graphene in situ, thereby obtaining a silicon-tin-carbon composite material. The silicon-tin-carbon composite material includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles; wherein a single silicon-tin-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer coating the inner core, and first gaps are distributed between the shell layer and the inner core; wherein the inner core includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework; and the shell layer includes a carbon layer.

[0175] Comparative Example 1

[0176] The difference from Example 1 is that the negative electrode material is pure silicon powder.

[0177] Comparative Example 2

[0178] The difference from Example 1 is that the negative electrode material is a single cyano gel, and the preparation method is as follows:

[0179] (1) First, a 0.6 mol / L SnCl4 ethanol solution (solution A) and a 0.6 mol / L InCl3 ethanol solution (solution B) were obtained by conventional methods. Then, silicon powder was ultrasonically dispersed in a 0.6 mol / L K2Ni(CN)4 ethanol solution (solution C) to obtain solution D. The mass concentration of silicon powder in solution D was 80 mg / mL.

[0180] (2) Solution A, solution B and solution D were mixed at 20°C in a molar ratio of Sn, In and Ni of 2:1:1, and 2 mol / L sodium borohydride solution was added for reduction reaction for 1 h. The obtained product was vacuum dried at 90°C for 20 h, and heated to 700°C at a rate of 3°C / min for annealing for 6 h. The annealed product was then repeatedly washed with distilled water and ethanol, and then dried.

[0181] Comparative Example 3

[0182] The difference from Example 1 is that no graphene carbon layer coating is performed, that is, there is no step S4.

[0183] Comparative Example 4

[0184] S1. Preparation of the first precursor:

[0185] (1) First, a 0.6 mol / L SnCl4 ethanol solution (solution A) and a 0.6 mol / L InCl3 ethanol solution (solution B) were obtained by conventional methods. Then, silicon powder was ultrasonically dispersed in a 0.6 mol / L K2Ni(CN)4 ethanol solution (solution C) to obtain solution D. The mass concentration of silicon powder in solution D was 80 mg / mL.

[0186] (2) Solution A, solution B and solution D were mixed at 20°C in a molar ratio of Sn, In and Ni of 2:1:1, and a 2 mol / L sodium borohydride solution was added for a reduction reaction for 1 hour. The obtained product was vacuum dried at 90°C for 20 hours, and the temperature was raised to 700°C at a rate of 3°C / min, and annealed for 6 hours. The annealed product was then repeatedly washed with distilled water and ethanol, and then dried to obtain a first precursor. The structure of the first precursor includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework.

[0187] S2, preparation of the second precursor: 8mL of silicon source and 3g of the first precursor obtained in step S1 were added with 250mL of 28wt% ammonia solution in sequence, mixed and stirred for 55min, filtered and cleaned, and pickled with 2mol / L hydrochloric acid, filtered and cleaned again, and dried; then, at 600℃, the heating rate was 3℃ / min, and the silicon dioxide layer was fixed by heat treatment for 15h to obtain the second precursor. The structure of the second precursor includes the first precursor and the silicon dioxide layer covering the first precursor; the first precursor includes a tin-based alloy frame and silicon particles, and the silicon particles are distributed in the tin-based alloy frame.

[0188] S4, adding the silica-coated second precursor obtained in step S2 and humic acid in a mass ratio of 100:15 into deionized water and mixing evenly, controlling the solid-liquid ratio at 1:12, then dripping a 28wt% ammonia solution under stirring until the humic acid powder is completely dissolved, then heating to 90°C and evaporating the solvent to make the humic acid evenly coat the surface of the second precursor; and sintering at 260°C in a microwave oven (microwave power of 1000W) for 8h, cooling to room temperature and taking out, and then placing in a tubular furnace under an inert atmosphere at a rate of 3°C / min from room temperature to 700°C for 15h, so that the humic acid is thermally decomposed to synthesize graphene in situ, and finally, removing the silica layer with a 5wt% HF solution to obtain a silicon-tin-carbon composite material. The silicon-tin-carbon composite material comprises silicon-tin composite particles and a graphene layer coated on the surface of the silicon-tin composite particles; the silicon-tin composite particles comprise a tin-based alloy frame and silicon particles, the silicon particles are distributed in the tin-based alloy frame, and gaps are distributed between the silicon-tin composite particles and the graphene layer.

[0189] Comparative Example 5

[0190] S1. Preparation of the first precursor:

[0191] (1) First, a 0.6 mol / L SnCl4 ethanol solution (solution A) and a 0.6 mol / L InCl3 ethanol solution (solution B) were obtained by conventional methods. Then, silicon powder was ultrasonically dispersed in a 0.6 mol / L K2Ni(CN)4 ethanol solution (solution C) to obtain solution D. The mass concentration of silicon powder in solution D was 80 mg / mL.

[0192] (2) Solution A, solution B and solution D were mixed at 20°C in a molar ratio of Sn, In and Ni of 2:1:1, and a 2 mol / L sodium borohydride solution was added for a reduction reaction for 1 hour. The obtained product was vacuum dried at 90°C for 20 hours, and the temperature was raised to 700°C at a rate of 3°C / min, and annealed for 6 hours. The annealed product was then repeatedly washed with distilled water and ethanol, and then dried to obtain a first precursor. The structure of the first precursor includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework.

[0193] S2, preparation of the second precursor: 8mL of silicon source and 3g of the first precursor obtained in step S1 were added with 250mL of 28wt% ammonia solution in sequence, mixed and stirred for 55min, filtered and cleaned, and pickled with 2mol / L hydrochloric acid, filtered and cleaned again, and dried; then, at 600℃, the heating rate was 3℃ / min, and the silicon dioxide layer was fixed by heat treatment for 15h to obtain the second precursor. The structure of the second precursor includes the first precursor and the silicon dioxide layer covering the first precursor; the first precursor includes a tin-based alloy frame and silicon particles, and the silicon particles are distributed in the tin-based alloy frame.

[0194] S3, preparation of the third precursor: 0.45mmol surfactant (hexadecyltrimethylammonium bromide) and 8mol deionized water were mixed and ultrasonically dispersed for 55min to form spherical micelles. A mixture of resorcinol (0.5mmol), formaldehyde (0.5mol) and sodium carbonate (0.009mmol) was added and stirred continuously. Subsequently, 4g of the second precursor obtained in step S2 was added, and then polymerized at 90℃ for 15h, and then vacuum dried at 90℃ for 18h, and then carbon coated at 650℃ for 15h under nitrogen atmosphere. Finally, the silicon dioxide layer was removed with 5wt% HF solution to obtain the third precursor. The structure of the third precursor includes silicon-tin-carbon composite particles; the silicon-tin-carbon composite particles have a core-shell structure, which includes a core and a shell layer covering the core; the core includes a tin-based alloy framework and silicon particles, the silicon particles are distributed in the tin-based alloy framework, and the shell layer includes a carbon layer; a first gap is distributed between the core and the carbon layer.

[0195] S4. The third precursor prepared in step S3 and humic acid are added to deionized water at a mass ratio of 100:15 and mixed evenly, and the solid-liquid ratio is controlled at 1:12. Then, a 28wt% ammonia solution is added dropwise under stirring until the humic acid powder is completely dissolved. The mixture is heated to 90°C and the solvent is evaporated to make the humic acid evenly coated on the surface of the third precursor. The mixture is sintered at 260°C in a microwave oven (microwave power of 1000W) for 8h, cooled to room temperature, taken out, placed in a tubular furnace under an inert atmosphere, heated from room temperature to 700°C at a rate of 3°C / min, and sintered for 15h in a second stage. The humic acid is thermally decomposed to synthesize graphene in situ to obtain a silicon-tin-carbon composite material. The silicon-tin-carbon composite material includes silicon-tin-carbon composite particles and a graphene layer coating the silicon-tin-carbon composite particles; the silicon-tin-carbon composite particles have a core-shell structure, which includes an inner core and a shell coating the inner core; the inner core includes a tin-based alloy framework and silicon particles, the silicon particles are distributed in the tin-based alloy framework, and the shell layer includes a carbon layer; a first gap is distributed between the inner core and the carbon layer.

[0196] Effect Example 1

[0197] The silicon-tin-carbon composite material prepared in Example 17 of the present invention includes a cluster structure and a graphite carbon layer covering the surface of the cluster structure, the cluster structure includes a plurality of silicon-tin-carbon composite particles; second voids are distributed between the silicon-tin-carbon composite particles; a single silicon-tin-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core, the inner core includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework; the shell layer includes a carbon layer; first voids are distributed between the shell layer and the inner core.

[0198] The silicon-tin-carbon composite materials prepared in Examples 1-16 of the present invention include a cluster structure and a graphene layer covering the cluster structure, the cluster structure includes a plurality of silicon-tin-carbon composite particles; second gaps are distributed between the silicon-tin-carbon composite particles; a single silicon-tin-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core, the inner core includes a tin-based alloy framework and silicon particles, and the silicon particles are distributed in the tin-based alloy framework; the shell layer includes a silicon-containing layer and a carbon layer; the silicon-containing layer is coated on the surface of the inner core, the carbon layer is coated on the surface of the silicon-containing layer, the first gaps are distributed between the silicon-containing layer and the carbon layer, and the carbon layer also includes nitrogen doping.

[0199] The inductively coupled plasma (ICP) method is used to test the element content (tin, carbon, oxygen and nitrogen content) in the tin-carbon composite material prepared by the present invention. The test method is as follows: (1) Pre-treatment by microwave digestion method, 0.5g of the tin-carbon composite material prepared in the embodiment or the comparative example is placed in a digestion tank, 3mL of concentrated nitric acid and 9mL of concentrated sulfuric acid are added in sequence with a liquid adder, and the mixture is shaken well; and the mixture is kept at a constant temperature of 160°C for 3min, 180°C for 3min, 200°C for 10min, and 220°C for 10min, and then cooled to room temperature, filtered with quantitative filter paper, and the filtrate is placed in a 50mL volumetric flask as the test solution; (2) The above test solution is tested in the PerkinElmer ICP spectrometer Avio™ 200 device; the test condition is an air pressure of 2.5MPa.

[0200] The D50 of the silicon-tin-carbon composite materials prepared in the examples and comparative examples was tested using a Malvern particle size tester.

[0201] The conductivity was measured at room temperature using an Orion Star™ A212 conductivity benchtop meter.

[0202] The average pore size of the silicon-tin-carbon composite materials obtained in the examples and comparative examples was tested using a pore size POROLUX Cito instrument.

[0203] The charge transfer resistance was measured by electrochemical impedance spectroscopy (compacted density 1.65 g / cm 3 )get.

[0204] The above physical and chemical results are shown in Table 1 below.

[0205] Table 1

[0206]

[0207] Table 1 continued

[0208]

[0209] Note: The content of each element indicates the percentage of the mass of each element in the mass of the silicon-tin-carbon composite material.

[0210] Effect Example 2

[0211] The preparation method of the button cell used for testing the electrochemical performance is as follows: the silicon-tin-carbon composite material prepared in the embodiment and the comparative example is mixed evenly with the conductive agent (KS-6), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a ratio of 95.5:1.5:1.5:1.5, and applied on a copper foil with a compaction density of 1.60 g / cm 3, vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte using 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, the separator is PE / PP / PE composite film, and assembled into a button battery.

[0212] The above button cell was subjected to various electrical performance tests on a blue battery tester, the test condition was 25°C, and the charging voltage limit was 0.005-2V.

[0213] (1) First discharge specific capacity and first coulombic efficiency

[0214] The charge and discharge were carried out at a rate of 0.1C, and the first discharge specific capacity and the first coulombic efficiency were tested. The test results are shown in Table 2.

[0215] (2) Cycle performance

[0216] The charge and discharge cycles were performed 300 times at a rate of 0.1C, and the 300th discharge specific capacity was recorded as the 300-cycle retention capacity. The test results are shown in Table 2.

[0217] Table 2

[0218]

[0219] (3) Rate performance

[0220] The test conditions for rate performance are: rate charge and discharge at a current density of 0.1C-3C, and the charging voltage is limited to 0.005-2V. The rate performance is tested at a current density of 0.1C. The results are shown in Table 3.

[0221] Table 3

[0222]

[0223] As shown in Table 2 and Table 3, compared with Comparative Examples 1-5, Examples 1-17 obtain a first precursor, then perform silicon dioxide coating, cluster structure preparation and carbon coating, obtain a cluster structure, and then perform graphene carbon coating to obtain a silicon-tin-carbon composite material. The silicon-tin-carbon composite material obtained in Examples 1-17 includes a cluster structure and a graphene layer coated on the cluster structure, and the cluster structure includes a plurality of silicon-tin-carbon composite particles; a single silicon-tin-carbon composite particle includes a tin-based alloy framework and a silicon particle, and a carbon layer. First, the unique three-dimensional structure of the tin-based alloy framework can effectively improve the volume expansion of silicon particles; in addition, the metal elements in the tin-based alloy framework can further improve the conductivity of the material; secondly, the gap between the core and the shell in the silicon-tin-carbon composite particles provides a second line of defense for the volume expansion of the silicon material; furthermore, the second gap between several silicon-tin-carbon composite particles further inhibits the volume expansion of the silicon material; finally, the in-situ coating of graphene enhances the conductivity and mechanical properties of the silicon-tin-carbon composite material, and further improves its volume expansion defect. Therefore, the silicon-tin-carbon composite material obtained in Examples 1-17 has better first coulomb efficiency, cycle performance and rate performance, and lower pole piece expansion rate than the silicon-tin-carbon composite material obtained in Comparative Examples 1-5.

Claims

1. A silicon-tin-carbon composite material, characterized in that: It includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of silicon-tin-carbon composite particles, and second gaps are distributed between the silicon-tin-carbon composite particles; Among them, a single silicon-tin-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core, and a first gap is distributed between the shell layer and the core; wherein the core includes a tin-based alloy frame and silicon particles, and the silicon particles are distributed in the tin-based alloy frame; the shell layer includes a carbon layer.

2. The silicon-tin-carbon composite material according to claim 1, characterized in that The silicon-tin-carbon composite material satisfies one or more of the following conditions AF: A. The D50 of the silicon-tin-carbon composite material is 400-550 nm, preferably 430-520 nm, for example 485, 481, 480, 475, 474, 470 or 465 nm; B. The average pore size of the silicon-tin-carbon composite material is 14-30 nm, preferably 17-27 nm, for example, 23.7, 23.4, 22.7, 22.4, 22.1, 21.7, 21.6, 21.2, 20.7, 20.6, 20.4, 20.3 or 19.2 nm; C. The silicon content of the silicon-tin-carbon composite material is 45%-50%, preferably 46%-49%, for example, 33.1%, 33.0%, 32.8%, 32.7%, 32.6%, 32.5%, 32.3%, 32.2%, 32.1%, 31.9%, 31.7%, 31.3% or 31.2%; D. The tin content of the silicon-tin-carbon composite material is 12%-24%, preferably 15%-21%, for example, 19.1%, 18.7%, 18.6%, 18.5%, 18.4%, 18.3%, 18.2%, 17.9%, 17.8%, 17.6%, 17.5%, 17.4% or 17.3%; E. The carbon content of the silicon-tin-carbon composite material is 18%-30%, preferably 20%-28%, for example 25.1%, 24.8%, 24.6%, 24.3%, 24.2%, 24.1%, 23.9%, 23.8%, 23.7%, 23.6% or 23.2%; F. The oxygen content of the silicon-tin-carbon composite material is 4%-10%, preferably 6%-8%, for example 7.86%, 7.69%, 7.56%, 7.55%, 7.42%, 7.30%, 7.06%, 7.02%, 6.99%, 6.82%, 6.75%, 6.68%, 6.57%, 6.54%, 6.43%, 6.35% or 6.30%; The content of each element mentioned above represents the percentage of the mass of each element to the mass of the silicon-tin-carbon composite material.

3. The silicon-tin-carbon composite material according to claim 1, characterized in that The silicon-tin-carbon composite material satisfies one or more of the following conditions AC: A. In a single silicon-tin-carbon composite particle, the tin-based alloy framework further includes a second metal; Wherein, the type of the second metal is preferably one or more of indium, platinum, iron, cobalt, germanium, antimony, palladium, nickel, cobalt and copper, such as indium and nickel; When the second metal is indium and nickel, the content of indium is preferably 3%-15%, more preferably 6%-12%, for example 9.5%, 9.4%, 9.3%, 9.2%, 9.1%, 8.9% or 8.8%; the content of nickel is preferably 20.4%-44.4%, more preferably 25%-28%, for example 9.5%, 9.4%, 9.3%, 9.2%, 9.1%, 8.7% or 8.6%; the content of indium or nickel is the percentage of the mass of indium or nickel to the mass of the silicon-tin-carbon composite material; B. In the single silicon-tin-carbon composite particle, the shell layer further comprises a silicon-containing layer; the silicon-containing layer covers the core, the carbon layer covers the silicon-containing layer, and a first gap is distributed between the silicon-containing layer and the carbon layer; C. In the single silicon-tin-carbon composite particle, the carbon layer further includes heteroatoms; Wherein, the type of the heteroatom is preferably one or more of nitrogen, phosphorus, sulfur and boron, such as nitrogen; Among them, the heteroatom content is preferably 0.1-0.65%, more preferably 0.2%-0.55%, for example 0.34%, 0.32%, 0.31%, 0.30%, 0.28%, 0.27%, 0.26%, 0.25%, 0.24%, 0.23% or 0.21%; the heteroatom content represents the percentage of the mass of the heteroatom to the mass of the silicon-tin-carbon composite material.

4. A method for preparing a silicon-tin-carbon composite material, characterized in that: It includes the following steps: S1, subjecting a mixed solution including tin chloride, transition metal cyanide and silicon source to reduction reaction, drying and annealing to obtain a first precursor; S2, coating the first precursor with silicon dioxide to form a silicon dioxide layer to obtain a second precursor; The aqueous dispersion of the second precursor and the oil phase solution containing an emulsifier are mixed, the solvent is removed, and heat-treated to obtain a third precursor; S3, carbon-coating the third precursor, removing the silicon dioxide layer, and obtaining a fourth precursor; S4, coating the fourth precursor with graphene to obtain a silicon-tin-carbon composite material.

5. The method for preparing the silicon-tin-carbon composite material according to claim 4, characterized in that: The preparation method of the silicon-tin-carbon composite material meets one or more of the following conditions AJ: In A and S1, the transition metal cyanide has the molecular formula A y M k (CN) z , A represents an alkali metal ion, M represents a central metal ion, CN represents a cyanide ion, the type of the alkali metal ion A is sodium, potassium or lithium; the y is preferably a natural number satisfying 0<y<3, such as 2; the type of the central metal ion M is preferably one or more of iron, cobalt, copper, nickel and platinum, such as nickel, copper or platinum; the k is preferably a natural number satisfying 0<y<2, such as 1; the z is preferably a natural number satisfying 2<z<9, such as 3 or 4; the transition metal cyanide is preferably one or more of potassium ferrocyanide, potassium ferrocyanide, potassium cobalt cyanide, potassium nickel cyanide, trisodium cuprous cyanide and dilithium platinum (IV) tetracyanide, such as potassium nickel cyanide, trisodium cuprous cyanide or dilithium platinum (IV) tetracyanide; In B and S1, the silicon source is one or more of silicon powder, silicon oxide and silicon monoxide, such as silicon powder; In C and S1, the molar ratio of tin in the tin chloride to the transition metal in the transition metal cyanide is (1-2):(0.5-1), preferably (1.5-2):(0.8-1), for example 2:1; D. In S1, the molar mass ratio of tin in the tin chloride to the silicon source is (0.1-0.5) mol:240 g, for example 0.36 mol:240 g; In E and S1, the reduction reaction time is 1-1.5 h, for example 1 h; In F and S1, the annealing treatment temperature is 650-900° C., for example, 700, 750, 800 or 850° C.; In G and S1, the rate of heating from room temperature to the temperature of the annealing treatment is 1-10°C / min, for example, 3°C / min; In H and S1, the annealing time is 5-8 hours, for example 6 hours; In I and S1, the mixed solution including tin chloride, transition metal cyanide and silicon source also includes a second metal chloride; Wherein, the second metal chloride is preferably one or more of indium chloride, platinum chloride, ferric chloride, cobalt chloride, germanium chloride, antimony chloride and palladium chloride, such as indium chloride; Wherein, the molar ratio of tin in the tin chloride to the second metal in the second metal chloride is preferably (1-2): (0.5-1), more preferably (1.5-2): (0.6-1.2), for example 2:1 or 2:0.8; In J and S1, the annealing treatment is followed by coating with a silicon-containing layer; Wherein, the coating of the silicon-containing layer is preferably carried out by coating the silicon source gas with a chemical vapor deposition method or an atomic layer deposition method; Among them, when the silicon-containing layer is coated, the type of silicon source gas is preferably one or more of tetraethoxysilane, methylsilane and ethylsilane, such as methylsilane; when the silicon-containing layer is coated, the working temperature is preferably 150-350°C, such as 250 or 300°C; when the silicon-containing layer is coated, the coating time is preferably 24-48h, such as 30h.

6. The method for preparing the silicon-tin-carbon composite material according to claim 4, characterized in that: The preparation method of the silicon-tin-carbon composite material meets one or more of the following conditions AN: A. In S2, the preparation method of coating the first precursor with silicon dioxide comprises the following steps: mixing the first precursor, a silicon source and an ammonia solution, acid washing, and heat treating; Wherein, the type of the silicon source is preferably silicate or silicate; the silicate is preferably ethyl orthosilicate and / or methyl orthosilicate; the silicate is preferably one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate; Wherein, the mass volume ratio of the first precursor, the silicon source and the ammonia solution is preferably (2-5) g: (3-10) mL: (240-260) mL, for example, 3 g: 8 mL: 250 mL; The temperature of the heat treatment is preferably 500-750°C, such as 600, 650 or 700°C; the time of the heat treatment is preferably 8-24h, such as 15h; the rate of heating from room temperature to the temperature of the second heat treatment is preferably 1-10°C / min, such as 3°C / min; B. In S2, the aqueous dispersion of the second precursor comprises a second precursor, a surfactant and water; Wherein, the type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide; Wherein, the ratio of the second precursor, the surfactant and the water is preferably (8-12) g: (0.3-0.8) mol: 300 mL, for example, 10 g: 0.55 mol: 300 mL; In C and S2, the type of the emulsifier is an emulsifier with a hydrophile-lipophile balance value of 3-8, preferably an emulsifier with a hydrophile-lipophile balance value of 4-7, and more preferably one or more of propylene glycol fatty acid ester, diethylene glycol monooleate, glyceryl monostearate and diethylene glycol monolaurate, such as diethylene glycol monooleate or propylene glycol fatty acid ester; In D and S2, the oil phase solvent in the oil phase solution containing the emulsifier is an olefin having 12 to 28 carbon atoms, such as 1-octadecene; In E and S2, the mass ratio of the second precursor to the emulsifier is 10:(0.15-0.30), for example, 10:0.18 or 10:0.24; In F and S2, the heat treatment temperature is 450-600°C, for example, 550°C; In G and S2, the heat treatment time is 0.5-1.5 h, for example, 1 h; In H and S3, the carbon coating temperature is 500-900°C, for example, 650 or 700°C; In I and S3, the carbon coating time is 8-24 hours, for example, 15 hours; In J and S3, the carbon source during carbon coating is phenolic resin and / or asphalt, such as phenolic resin fixed by surfactant; In K and S3, the carbon-coated carbon source further includes heteroatoms; In L and S4, the carbon source used in the graphene carbon coating is humic acid; Wherein, when the carbon source is humic acid, the graphene carbon coating is preferably performed by first mixing the fourth precursor, humic acid and water, and then dropping an ammonia solution under stirring conditions to remove the solvent; In M and S4, the mass ratio of the fourth precursor to the carbon source during the carbon coating of the graphene is 100:(10-18), preferably 100:(11-18), for example 100:15 or 100:12; In N and S4, the graphene carbon coating is subjected to a first-stage sintering, cooling and a second-stage sintering, and the temperature of the second-stage sintering is higher than the temperature of the first-stage sintering; The temperature of the first sintering step is preferably 200-350°C, such as 260 or 280°C; the time of the first sintering step is preferably 6-12h, such as 8h; the first sintering step is preferably performed in a microwave oven; the power of the microwave oven is preferably 800-1100W, such as 1000W; Among them, the temperature of the second stage sintering is preferably 600-900°C, such as 700 or 750°C; the time of the second stage sintering is preferably 8-24h, such as 15h; the rate of heating from room temperature to the temperature of the second stage sintering is preferably 1-10°C / min, such as 3°C / min.

7. The method for preparing the silicon-tin-carbon composite material according to claim 6, characterized in that: The method for preparing the silicon-tin-carbon composite material satisfies the following conditions A and / or B: In A and S3, when the carbon source during carbon coating is phenolic resin, the preparation method of carbon coating the third precursor comprises the following steps: mixing resorcinol, formaldehyde, a catalyst and the third precursor, polymerizing and carbon coating; Wherein, the molar ratio of the formaldehyde to the resorcinol is preferably (500-1500): (0.5-1.5), such as 1000:1 or 625:1; the catalyst is preferably a base, more preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium carbonate; the molar ratio of the resorcinol to the catalyst is preferably (0.5-1.5): (0.007-0.03), such as 0.5: 0.009 or 0.8: 0.009; the molar mass ratio of the resorcinol to the third precursor is preferably (0.5-1.5) mmol: (3-4.5) g, such as 0.5 mmol: 4.0 g, 0.8 mmol: 4.0 g or 0.5 mmol: 3.5; the temperature of the polymerization reaction is preferably 80-100°C, such as 85 or 90°C; the time of the polymerization reaction is preferably 8-24h, such as 15h; Alternatively, in S3, when the carbon source during carbon coating is a phenolic resin fixed with a surfactant, the preparation method of carbon coating the third precursor comprises the following steps: mixing an aqueous solution of a surfactant, resorcinol, formaldehyde, a catalyst and the third precursor, polymerizing and carbon coating; Wherein, the type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide; Wherein, the molar ratio of the surfactant to the resorcinol is preferably (0.3-0.65):(0.5-1.5), such as 0.45:0.5, 0.55:0.5 or 0.45:0.8; In B and S3, when a heteroatom is added to the carbon source during the carbon coating, the preparation method of carbon coating the third precursor comprises the following steps: mixing the heteroatom source, resorcinol, formaldehyde, a catalyst and the third precursor, polymerizing and carbon coating; Wherein, the type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; when the type of the heteroatom is nitrogen, the type of the nitrogen source is preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as melamine; Wherein, the molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-1.5), for example, 0.03:0.8 or 0.03:0.

5.

8. A silicon-tin-carbon composite material, characterized in that: The silicon-tin-carbon composite material is prepared by the preparation method of any one of claims 4 to 7.

9. A pole piece, characterized in that: It comprises the silicon-tin-carbon composite material as claimed in claims 1 to 3 or claim 8.

10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 9.

Citation Information

Patent Citations

  • Pre-magnesium silicon monoxide negative electrode material, preparation method thereof and lithium ion battery

    CN118373427A